Tuberculous arthritis: negative Xpert MTB/RIF assay does not rule out infection!. (29th June 2018) - Davis, Rebecca; Higgens, Clare; Cosgrove, Catherine; Shur, Joshua; Arkell, Paul
Abstract : We present a case of a 31-year-old man of Indian origin with no previous medical history who presented with an inflamed knee. Treatment for bacterial infection was unsuccessful, and needle aspiration of the left knee effusion/collection was smear and culture positive for tuberculosis (TB), despite Xpert MTB/RIF being falsely negative. The patient was commenced on quadruple therapy for TB and within 2 months had improved significantly with no clinical evidence of ongoing inflammation.